2011
DOI: 10.1152/ajpregu.00764.2010
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein β-deficiency enhances type 1 diabetic bone phenotype by increasing marrow adiposity and bone resorption

Abstract: Motyl KJ, Raetz M, Tekalur SA, Schwartz RC, McCabe LR. CCAAT/enhancer binding protein ␤-deficiency enhances type 1 diabetic bone phenotype by increasing marrow adiposity and bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 67 publications
3
28
1
Order By: Relevance
“…Osteoblasts of C/EBPβ knockout mice displayed impaired differentiation and functional deficiency (Tominaga et al, 2008;Smink et al, 2009), including both cell autonomous and noncell autonomous mechanisms (Smink et al, 2009;Zanotti et al, 2009). Moreover, type 1 diabetes-induced bone mass reduction is further diminished in C/EBPβ-deficient mice and diabetic C/EBPβ-deficient mice displayed an enhanced adiposity in the bone marrow (Motyl et al, 2011). However, in this study no difference in bone formation parameters was shown.…”
Section: C/ebpβ In Osteoblastscontrasting
confidence: 59%
“…Osteoblasts of C/EBPβ knockout mice displayed impaired differentiation and functional deficiency (Tominaga et al, 2008;Smink et al, 2009), including both cell autonomous and noncell autonomous mechanisms (Smink et al, 2009;Zanotti et al, 2009). Moreover, type 1 diabetes-induced bone mass reduction is further diminished in C/EBPβ-deficient mice and diabetic C/EBPβ-deficient mice displayed an enhanced adiposity in the bone marrow (Motyl et al, 2011). However, in this study no difference in bone formation parameters was shown.…”
Section: C/ebpβ In Osteoblastscontrasting
confidence: 59%
“…Osteoblasts between the second and the fourth passages were used in all experiments to be seeded on the implants with a density of 1 Â 10 6 cells/ml and randomized to incubate with the following factors respectively: (1) TI treated with normal serum (NS); (2) TI treated with diabetic serum (DS); (3) CTI treated with DS; (4) TI treated with DS þ N-acetyl-L-cysteine (NAC, a ROS inhibitor, 20 mmol/L; Sigma, MO); (5) CTI treated with DS þ LY294002 (a PI3K inhibitor, 20 mmol/L; Sigma, MO). The diabetic mice were induced by intravenous injection of STZ (40 mg/kg, Sigma, MO) for 5 consecutive days as described previously [27] and confirmed with blood glucose greater than 300 mg/dl 15 days post-first injection. The DS was acquired from diabetic rats.…”
Section: Osteoblast Isolation and Culturementioning
confidence: 99%
“…This finding concurs with another study that reported lower bone mineral density and BAT mass in women with anorexia nervosa [44] . Interestingly, studies conducted in animal models with defective brown adipogenesis also showed a reduced bone mass [45,46] . Intervention studies are warranted to elucidate whether BAT activation induces improvement in bone mineral density, and whether BAT can be used as an anti-osteopenia and osteoporosis treatment.…”
Section: Importance Of Activating Batmentioning
confidence: 99%